Aplikasi Metode Self Potential untuk Pemetaan Sebaran Lindi di Wilayah Tempat Pembuangan Akhir (TPA) Putri Cempo Surakarta - Andri Wasis Handoko; D Darsono; D Darmanto (Department of Physics, Sebelas Maret University, 2016)
The distribution of leachate and the pattern of fluid flow in Tempat Pembuangan Akhir (TPA) Putri Cempo were mapped by utilizing the Self Potential method. Data acquisition was done before and after the rain with a fixed base techniques with 10 meters interval distance with total number of observations were 78 points for data acquisition. SP Data were processed using Surfer 11 software to generate the isopotential contours. It is found that the leachate distribution anomaly is indicated only for after the rain observation. Interpretation was done by Rao and Ram Babu Theory. The result of vertical spreading of anomalous 1 was found at the depth of the upper end (h) 5.45 meters, the depth of the lower end (H) 17.62 meters and the angle of anomaly (θ) 840 while the anomalous 2 was found at the depth of the upper end (h) 5.45 meters, the depth of the lower end (H) 11.22 meters and the angle of anomaly (θ) 73.70. At the time before the rain, the pattern of fluid flow leading to the eastern part of the research area, while after the rain, the fluid flow coming from two directions, from the west and from the east of the research area leading to the central part of the research area.